Refurbishment projects : health and safety management - Oloke, David (ICE Publishing, 2020)
This volume is a qualitative reference tool for exploring health and safety management and risk management of alteration, renovation and refurbishment projects. As the need to make old stock more energy efficient increases in line with the requirements of sustainable development, the number of extentions, loft conversions, basement constructions and other retrofit projects has increased. The title explores the planning of alteration and refurbishment construction projects, involving analysis of the existing structure, end-of-lifecycle operations and the safety risks of potentially unknown conditions.